Designing research with qualitative comparative analysis (QCA): approaches, challenges, and tools - Thomann, Eva; Maggetti, Martino (Sociological methods and research, 2020)
Recent years have witnessed a host of innovations for conducting research with qualitative comparative analysis (QCA). Concurrently, important issues surrounding its uses have been highlighted. In this article, we seek to help users design QCA studies. We argue that establishing inference with QCA involves three intertwined design components: first, clarifying the question of external validity; second, ensuring internal validity; and third, explicitly adopting a specific mode of reasoning. We identify several emerging approaches to QCA rather than just one. Some approaches emphasize case knowledge, while others are condition oriented. Approaches emphasize either substantively interpretable or redundancy-free explanations, and some designs apply an inductive/explorative mode of reasoning, while others integrate deductive elements. Based on extant literature, we discuss issues surrounding inference with QCA and the tools available under different approaches to address these issues. We specify trade-offs and the importance of doing justice to the nature and goals of QCA in a specific research context.